Arch form: A review - Singh, Disha (International journal of health sciences, 2021)
Arch form is highly individualized .The universal ideal arch form is the most persistent but exclusive task for most of the orthodontic researchers have. The basic principle of arch form in orthodontic treatment is that within reason, the patient original arch form should be preserved. Dental arch width and form are important Factors for determining the success and stability of orthodontics treatment. Because of the complex problems, And relatively low knowledge of dental arches, as of today, there is no universally accepted ideal arch form. This article gives the review about different concept of arch form, importance arch form from conventional era to modern practice.